2012
DOI: 10.1186/1471-230x-12-1
|View full text |Cite
|
Sign up to set email alerts
|

Low incidence of positive smooth muscle antibody and high incidence of isolated IgM elevation in Chinese patients with autoimmune hepatitis and primary biliary cirrhosis overlap syndrome: a retrospective study

Abstract: BackgroundUp to now, few data are available regarding the clinical characteristics of autoimmune hepatitis and primary biliary cirrhosis overlap syndrome. The study was to investigate and analyze the prevalent and clinical features of Chinese patients with this disease.MethodsClinical data on patients diagnosed as autoimmune hepatitis and primary biliary cirrhosis overlap syndrome in our hospital from January 2001 to December 2006 were collected and analyzed.ResultsOverlap syndrome of autoimmune hepatitis and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
57
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 93 publications
(66 citation statements)
references
References 21 publications
7
57
2
Order By: Relevance
“…In general, our patients fulfill the criteria of the PBC-AIH overlap syndrome described in western cohorts, although the prevalence of ASMA positivity is lower, a finding which also occurred in another study of Chinese patients [39] and noted in our previous multi-center study [30]. PBC patients with AIH features in our study demonstrated diminished 5-year adverse outcome-free survival than patients with classical PBC (58 vs. 81 %, p=0.038), a result comparable to that of Silveira et al [40] while inconsistent with that of Joshi et al [28].…”
Section: Discussionsupporting
confidence: 59%
“…In general, our patients fulfill the criteria of the PBC-AIH overlap syndrome described in western cohorts, although the prevalence of ASMA positivity is lower, a finding which also occurred in another study of Chinese patients [39] and noted in our previous multi-center study [30]. PBC patients with AIH features in our study demonstrated diminished 5-year adverse outcome-free survival than patients with classical PBC (58 vs. 81 %, p=0.038), a result comparable to that of Silveira et al [40] while inconsistent with that of Joshi et al [28].…”
Section: Discussionsupporting
confidence: 59%
“…In HLA-B27 transgenic rats, a highcalcium diet inhibited diarrhea and intestinal permeability 52 . Mice with dextran sulfate sodiuminduced colitis had firmer stools, less blood loss, and weight recovery following administration of the active form of vitamin D 53 . Vitamin D was shown to promote epithelial cell resistance to injury and suppress the inflammatory response to luminal antigens.…”
Section: Nutrient-dependent Regulation Of Intestinal Inflammation In mentioning
confidence: 97%
“…Within the immune system, 1,25-dihydroxyvitamin D 3 (1,25(OH)D 3 ) inhibits T helper-1 type immune function in cells, induces T regulatory cells, and enhances phagocytosis by white blood cells [11]. 1,25(OH)D 3 targets more than 900 genes [12], some of which are involved in intestinal homeostasis [13], which may play a role in IBD development [9,14]. In humans, early life nutrition [15] and season of birth [16] have been linked to later risk of developing IBD, indicating that a critical window for nutritional interventions to lower the risk of developing IBD exists.…”
Section: Introductionmentioning
confidence: 99%